Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Tematik Terpadu Menggunakan Model Pembelajaran Berbasis Komputer Tipe Tutorial di Kelas IV SDN 01 Benteng Pasar Atas - Azrial, Yulfian; Zuryanti, Zuryanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the improvement in student learning outcomes using a computer-based learning model tutorial type on integrated thematic learning in class IV SDN 01 Benteng Pasar Atas. This research is a classroom action research (CAR) that uses quantitative and qualitative approaches which are carried out in two cycles. The research subjects were teachers and grade IV SDN 01 Benteng Pasar Atas with 30 students. This research was conducted in two cycles, cycle I two meetings and cycle II one meeting. The results showed an increase in 1) The average assessment of the RPP cycle I 83.33% (B) and the second cycle 94.44% (SB), 2) The average observation of the implementation of learning aspects of the first cycle teachers 81.25% (B ) and the second cycle 93.75% (SB), 3) The average observation of the implementation of learning aspects of students cycle I 81.25% (B) and the second cycle 90.62% (SB), 4) Average learning outcomes learners knowledge aspects of the first cycle 69.80 (B) and second cycle 80.05 (B +), 5) The average learning outcomes of the students aspects of the first cycle skills 72.09 (B) and second cycle 80.00 (B) . Thus the computer-based learning model can significantly improve student learning outcomes in integrated thematic learning.